2020
DOI: 10.5937/zbdght2001022d
|View full text |Cite
|
Sign up to set email alerts
|

Apprising the local and global implication of ambient air Quality Index of Kaduna Metropolis, Nigeria

Abstract: This study apprises the local and global implication of ambient air quality index of Kaduna Metropolis, Nigeria. With the point of investigating the spatial and transient dissemination of the Air Quality Index (AQI) of Carbon monoxide (CO), Sulfur dioxide (SO 2), and Particulate Matter (PM 10) and their suggestions on human wellbeing, in view of neighborhood and global measures. Data were collected during the raining season and dry harmattan weather. From traffic, Industrial, commercial and residential areas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Recently, WHO [ 8 ] reported that 91% of premature deaths due to ambient air quality occur in both cities and rural areas of low and middle-income countries. The observed poor air quality in the urban areas is in line with various studies across the country e.g., Schwela [ 38 ], Lawal and Asimiea [ 39 ], Aliyu, Botai [ 40 ], Aliyu and Botai [ 41 ], Obanya, Amaeze [ 42 ], Daful, Adewuyi [ 43 ].…”
Section: Discussionsupporting
confidence: 87%
“…Recently, WHO [ 8 ] reported that 91% of premature deaths due to ambient air quality occur in both cities and rural areas of low and middle-income countries. The observed poor air quality in the urban areas is in line with various studies across the country e.g., Schwela [ 38 ], Lawal and Asimiea [ 39 ], Aliyu, Botai [ 40 ], Aliyu and Botai [ 41 ], Obanya, Amaeze [ 42 ], Daful, Adewuyi [ 43 ].…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have been carried out to study the impact of air quality in the environment. For example, [31] analyzes the varying spatial relationship between air pollutants [Carbon monoxide (CO), Sulphur dioxide (SO2), Carbon dioxide (CO2) and Particulate Matter (PM2.5 and PM10)] in Kaduna metropolis. The study was aimed at having more insight into be characteristics of air pollutants in the study area, which was geared towards efficient environmental management of the city.…”
Section: Introductionmentioning
confidence: 99%